La femme migrante comme agent de contrôle social dans le contexte de la frontière américaine. La Virginie au xviie siècle et la Californie à l’époque de la ruée vers l’or - Camille Marion (Transatlantica)
This article focuses on projects aiming to entice British or Anglo-American women to migrate to Virginia in the seventeenth century and to California during the Gold Rush in order to balance an extremely high male to female sex ratio and to stabilize areas recently disrupted by extreme demographic transformations following predominantly male waves of migration. Two of these projects are under study: the Virginia Company’s “maids for wives” project in 1621, and Eliza Farnham’s 1849 personal initiative for California. These projects sought to trigger waves of female migration in order to guarantee a renewal of the population and the survival of the settlement, as well as influence the development of these societies into a model reflecting the norms and mores of those they migrated from. This article examines women’s status as agents of social control as well as the evolution of this image between these two stages of American history, and thus the role and sphere of action expected of migrant women. Finally, this article explores the perception of women and the family as crucial to the creation and perpetuation of societies with European mores in the context of westward migrations.